Three-Phase inverter Controlled by ISCPWM and DPWM-S1 - Aghion, C.; Ursaru, O. (Elektronika ir Elektrotechnika, 2012)
This paper presents the implementation of the ISCPWM-DPWM-S1 control technique on a microcontroller. This technique was developed due to the modulation of a discontinuous signal DPWM-S1 with an inverted sinusoidal signal ISCPWM. Good results were obtained for the switching losses on the power transistors, which are lower, and for the amplitudes of the fundamental frequency, which are higher for the phase and line voltages. Ill. 9, bibl. 7 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1370